SOCIAL SUPPORT IN ACCESSING ADOLESCENTS MENTAL HEALTH SERVICES - Khoiriyah Isni; Winda Yulia Nurfatona; Nurul Qomariyah (Universitas Airlangga, 2023)
Introduction: The survey reported that adolescents experienced severe depression (15.6%) and extreme stress (6.3%) in Warungboto, Yogyakarta, Indonesia. In fact, with this condition, they are reluctant to access mental health services. Adolescents' skills still lacking in problem-solving and inadequate social support are thought to be the triggering factors for low access to health services. Aims: to determine the social support for adolescents in accessing mental health services. Methods: This type of research is quantitative research with a cross-sectional approach. The unit of analysis is adolescents (15-24 years) who are identified as having stress and depression based on the results of early detection of mental health. The sample size is 36 teenagers, with a total sampling technique. The variables are family support, peer support, mental health status, problem-solving, and self-control measured in the questionnaire. Meanwhile, mental health status was assessed using DASS-21 and PSS-10. Results: There was a significant relationship between social support from family (p-value 0.001, 95% CI 1.581-76.551) and peers (p-value 0.018, 95% CI 1.108 – 2.608) with adolescent mental health status. Adolescents with depression and stress are very few who get good social support from their families in accessing mental health services. This study proves that family social support is a significant factor in accessing mental health services. Conclusion: Family involvement in overcoming adolescent mental health problems is crucial. However, health providers can also provide community-based mental health services with a peer approach.